Ambulatory physical activity during the initial training phase in a Naval Commando Unit. Issue 4 (13th October 2015) - Epstein, Danny; Furman, M; Borohovitz, A; Iversen, Z; Shapira, S; Yanir, Y; Ofir, D
Abstract : Background: There is a positive correlation between the volume of physical activity performed and the incidence of lower extremity overuse injuries. Difficulty in evaluating the amount of activity in which highly specialised military units are engaged has prevented the implementation of a strict training programme designed to minimise overuse injuries. Purpose: To quantify the ambulatory physical activity performed by trainees during the initial training phase in a Naval Commando Unit, with a view to developing more exact physical performance guidelines for the unit and the Israel Defense Forces, in general. Methods: Twenty-four accelerometers were worn by two teams each day. Trainees were instructed to wear the device on their non-dominant wrist 24 h a day, during all types of activities. Twice a week, the devices were collected, checked for damage and recharged, and the data were transferred to a computer. Results: Six trainees failed to complete the 9-week training period. Of the total 1512 accelerometer-days, 1075 readings (71%) were included in the study data. Trainees ambulated on average a distance of 15.5±8.61 km/day and 95.5 km/week. Accelerometer readings (estimated distances) were averaged each week for the two teams. The total distance measured over the 9-week study period was 911.15 km in team A and 808.38 km in team B. The total distance measured in both teams was, thus, almost double the planned 440 km (p=0.001). Conclusions: Trainees greatly exceeded the planned safe distance. High variability was observed between trainees from the same team.